“Projeto Cão Pipoca: os impactos da presença de cães terapeutas em sala de espera da perspectiva de funcionários, estagiários e professores supervisores em uma Clínica Escola” - Keiserman, Boris Brancaglion (2019)
The following doctoral thesis considers the use of Animal Assisted Activities as a means to humanize a heath-promoting setting, to promote and encourage well-being and as a social catalyst. The following thesis considers the effects of the presence of therapy dogs in a Teaching Uni-versity Clinic located in the city of São Paulo, Brazil investigated by inter-viewing the health-promoting professionals. A team composed of un-dergraduate interns, supervising professors, a multidisciplinary team, and employees who had contact with the dogs during the process of Physical Therapy for children and adolescents with Duchenne Muscular Dystrophy. Set up as a Case Study, we aim to investigate how this group of workers perceive the presence of these animals and which changes occurred throughout the project. We used data triangulation composed of intern re-ports and semistructured interviews which were both analysed using lexi-cal analysis software IRaMuTeQ as a basis for thematic classes and hie-rarchic analysis, and an ethnographic diary was used as to better describe the Case itself. Results of the Case Study point to a few benefits of Animal Assisted Activities such as: the humanization of the waiting room, increase in comunication between the multidisciplinary team, the dogs as social and comunicational catalysts within an institutional environment, and the rela-tion between the dogs and their main care-provider as a model relations-hip. We also propose to decrive the relation between the dogs and their main provider as a non-verbal trust-based relation, named Therapeutic Link and we describe the limitations of the intervention within the studied case. We conclude, within the limitations of the Case Study that the the resence of therapy dogs was beneficial as a catalyst and a force that pro-moted unity in the employees and health professionals. We have conclu-ded that only the presence of therapy dogs does not guarantee the sucess of such a complex therapy model with a Duchenne Muscular Dystrophy population